Buku saku hematologi Larry Waterbury; Ahli Bahasa Sugi Suhandi; Editor W.Susiani Wijaya, Alexander H. Santoso - WATERBURY, Larry; Suhandi, Sugi; Wijaya, W. Susiani; Santoso, Alexander H (2001)
ix, 206 hlm 19 cm